Una edición contrahecha de las Obras en Prosa y Verso de Jacinto Polo de Medina - Rodríguez Domínguez, Guadalupe (Revista General de Información y Documentación, 2009)
One of de most persistent editorial phenomenon in the spanish press during XVII century is the publishing and releasing of pirate, contrafacta editions, or published texts without printing licenses or authorizations from books that were best sellers in their original version. Jacinto Polo de Medina was one of those authors whose books were so good accepted for the public that was necessary to print them so many times during the century. Academias del Jardín was his first book released in 1630. Since then his texts were often printed: Ocios de la soledad, El buen humor de las musas, A Lelio gobierno moral, Bureo de las musas y honesto entretenimiento para el ocio, Hospital de incurables, Universidad de amor y escuelas de interés, Fábula de Apolo y Daphne, y Obras en prosa y en verso. We have found a contrafacta edition of the last one, that is studied and described in this work.